Can Graph Neural Networks Learn to Solve the MaxSAT Problem? (Student Abstract) - Liu, Minghao; Huang, Pei; Jia, Fuqi; Zhang, Fan; Sun, Yuchen; Cai, Shaowei; Ma, Feifei; Zhang, Jian (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
The paper presents an attempt to bridge the gap between machine learning and symbolic reasoning. We build graph neural networks (GNNs) to predict the solution of the Maximum Satisfiability (MaxSAT) problem, an optimization variant of SAT. Two closely related graph representations are adopted, and we prove their theoretical equivalence. We also show that GNNs can achieve attractive performance to solve hard MaxSAT problems in certain distributions even compared with state-of-the-art solvers through experimental evaluation.